Optimalisasi Sistem Informasi Administrasi Digital Untuk Meningkatkan Efisiensi Layanan dan Keamanan Informasi Organisasi - Darmansah, Tengku; Pasaribu, Gusti Aprila; Juliani, Duwi; Pulungan, Syarah Nabila; Pangolangan, Cindy Aulia (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Digital transformation in the administration sector is an urgent need in the modern era, especially in terms of managing correspondence. This study aims to develop a digital administration information system that can improve service efficiency and information security in an organizational environment. Manual paper-based systems often cause various obstacles such as delays, data loss, and potential information leaks. The digital information system developed uses a centralized database, encryption, user authentication, and automatic notifications to support process efficiency. It is also equipped with mail tracking features, electronic archives, and role-based access control. This study also highlights system integration with other platforms such as financial and personnel systems to strengthen the organization’s digital ecosystem. The results of the system development show significant improvements in service speed, information security, and transparency in document management.